The bee Tetragonula builds its comb like a crystal. Issue 168 (22nd July 2020) - Cardoso, Silvana S. S.; Cartwright, Julyan H. E.; Checa, Antonio G.; Escribano, Bruno; Osuna-Mascaró, Antonio J.; Sainz-Díaz, C. Ignacio
Abstract : Stingless bees of the genus Tetragonula construct a brood comb with a spiral or a target pattern architecture in three dimensions. Crystals possess these same patterns on the molecular scale. Here, we show that the same excitable-medium dynamics governs both crystal nucleation and growth and comb construction in Tetragonula, so that a minimal coupled-map lattice model based on crystal growth explains how these bees produce the structures seen in their bee combs.